Customized CAD-CAM fabrication of occlusal splints - Anitua, Eduardo (2022)
The production of occlusal splints using the conventional technique based on a monomer and polymer mixing with subsequent curing of the mixture may leave traces of monomer that generate hypersensitivity reactions in allergic people to these chemicals. Hence, the use of CAD-CAM technology can improve the fit and comfort related to the use of the device on the patient. In this article a splint elaboration method is shown based on this technology.